Convenience bankingn ; Woman, you've come a long way ; Mrs. Fields [videorecording] - Lazaro, Cheche (The Probe Team, 1995)
Looks into the banking service called ATM (Automated Teller Machine) with its transaction fees ; women today with their evolving newer and more challenging roles and Mrs. Fields with her cookie business with 600 brank, a multi-dollar empire in only 19 years.